1993
DOI: 10.1099/0022-1317-74-7-1341
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relatedness of hepatitis B viral strains of diverse geographical origin and natural variations in the primary structure of the surface antigen

Abstract: A 681 nucleotide fragment of the hepatitis B virus (HBV) genome was sequenced that corresponded to the complete gene for hepatitis B surface antigen (HBsAg) in 80HBsAg-and hepatitis B e antigen (HBeAg)-positive sera of diverse geographical origins. These and 42 previously published HBV sequences within the S gene were used for the construction of a dendrogram. In this comparison, each of the 122 HBsAg genes was found to be related to one or other of the six previously identified genomic groups of HBV, A to F.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
292
2
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(322 citation statements)
references
References 39 publications
19
292
2
2
Order By: Relevance
“…Comparison of the pre-OLT sequences of the 20 patients with 88 published sequences 16 showed that the predominant HBV genotype and subtype were A (9 patients) and adw2 (12 patients), respectively. Mutations were defined as rare if they were present in 1 to 2, and unique if they were absent in the 88 published sequences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of the pre-OLT sequences of the 20 patients with 88 published sequences 16 showed that the predominant HBV genotype and subtype were A (9 patients) and adw2 (12 patients), respectively. Mutations were defined as rare if they were present in 1 to 2, and unique if they were absent in the 88 published sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen patients (patients 1-13) became HBsAg-positive again while they were still receiving HBIG; 7 (patients [14][15][16][17][18][19][20] became HBsAg-positive after discontinuation of HBIG. Reinfection occurred after a mean of 8.5 Ϯ 1.5 months (range, 1-20 months) post-OLT.…”
Section: Methodsmentioning
confidence: 99%
“…These genotypes have a distinct geographical distribution, with genotypes A (HBV/A) and HBV/ D predominant in Europe, Middle East, Central Asia, Siberia, and America, HBV/B and HBV/C in East Asia, and HBV/E in Africa. In addition, HBV/F has been reported in Central America, and HBV/G in the United States and France [Norder et al, 1993;Lindh et al, 1997;Sanchez-Tapias et al, 2002;Chu et al, 2003;Miyakawa and Mizokami, 2003;Deversa et al, 2004;Mulders et al, 2004;Tallo et al, 2004]. In Japan, HBV/C is the most prevalent, followed by HBV/B, while others are encountered very rarely.…”
Section: Introductionmentioning
confidence: 99%
“…However, HBsAg exposure, together with the fact that HBV has a mutation rate ten times higher than that of other DNA viruses 15 , favors the emergence of mutations in the surface (S) gene. Data regarding the primary structure of HBsAg in different regions of the world are important for the understanding of failure of protection with current vaccines 21 .…”
Section: Introductionmentioning
confidence: 99%